Analysis of the relationship between financial development and economic growth in the EU countries - Edmunds Čižo; Olga Lavrinenko; Svetlana Ignatjeva (Insights into Regional Development)
To what extent does financial development determine economic growth? Despite the obvious relationship between the level of financial development and economic growth rates, there is still no consensus on the significance and focus of this relation. Is there a directed impact of the level of financial development on economic growth, or does the development of a financial sector follow economic growth? Or is the relation between financial development and economic growth bidirectional? The aim of the research is to analyze the causal relationship between quantitative and dynamic differences in financial development and economic growth in the EU countries in the period 1995 - 2017. The period of the research from 1995 to 2017 is determined by the availability of financial development indicators for the EU countries. In order to prove the directed impact of the level of financial development on economic growth in the EU countries in the period 1995-2017, the average values of growth in the financial development index with the lag forwarding by one year, with the lag falling behind by one year, without the lag, and average values of the GDP growth per capita were analyzed.